Extended-stay lodging: A new high-return product - Berg, Peggy; Skinner, Mark (Acta Structilia, 1997)
In the USA a relatively new real estate product called extended-stay lodging should become as established a financial asset as limited-service hotels or apartment complexes. The potential for superior financial performance is based on assumptions of tightly controlled development costs, rapid ’lease-up,• high occupancy, and low operating expenses. The lower end of the extended-stay market has been pioneered by apartment companies, while the mid-market is being promoted by hotel companies that have recently entered the picture.